Body mass index does not affect response of rituximab in patients with rheumatoid arthritis: results from the TURKBİO registry - Karatas, Ahmet; Piskin Sagir, Rabia; Koca, Suleyman Serdar; Dalkilic, Ediz; Can, Gercek; Pehlivan, Yavuz; Onen, Fatos (Tubitak Scientific & Technological Research Council Turkey, 2023)
Background/aim: Adipose tissue produces several inflammatory mediators. Thus, obesity affects the disease course and the responses to the antirheumatic agents in inflammatory diseases. The aim of the study was to determine whether the body mass index (BMI) is involved in the response to rituximab in rheumatoid arthritis (RA).Materials and methods: This multicenter retrospective study included 206 RA patients who received rituximab from the Turkish Biologic (TURKBIO) registry between 2011 and the end of May 2017. Demographic and clinical data including age, sex, disease type, disease duration, and previous or current treatment with disease-modifying antirheumatic drugs (DMARDs) and biological drug durations are stored in the databse. Patients with a BMI >= 30 kg/m(2) were classified as obese, and patients with a BMI <30 kg/m(2) were classified as nonobese. Kaplan-Meier survival analysis was performed to estimate the drug survival. The subgroups were compared using the log-rank test.Results: The mean BMI of 206 patients included in the study was 27.05 (17.2-43.4) kg/m(2). There were 59 (28.6%) patients in the obese group and 147 (71.4%) patients in the nonobese group. The mean age, female percentage, and baseline disease activity score 28 (DAS28) were higher in the obese group than in the nonobese group. However, the Delta DAS28 at both 6 and 12 months were not significantly different between the groups (p = 0.785 and p = 0.512, respectively). Patient pain Visual Analogue Scale (VAS), patient fatigue VAS, and patient global VAS scores were also significantly higher at baseline in the obese group (p = 0.003, p = 0.006, and p = 0.006, respectively). However, no significant difference was found in terms of changes in patient pain VAS, patient fatigue VAS, patient global VAS and physician global VAS scores at 6 and 12 months compared to those at baseline. Rituximab treatment was ongoing for 71.2% of the obese and 63.3% of the nonobese patients (p = 0.279). The median drug survival duration was 77 months in the obese group and 62 months in the nonobese group (p = 0.053). The estimated drug survival rates for rituximab were not statistically significantly different in the obese and nonobese groups. Rituximab-related side effects were also similar between the groups.Conclusion: In obese and nonobese patients with RA, rituximab treatment exhibits similar side effects and similar long-term efficacy. These results suggest that obesity does not alter drug survival for rituximab and response rates, in RA and rituximab may be a favorable treatment agent in patients with RA and obesity.
Keywords: Body mass index; drug survival; obesity; rheumatoid arthritis; rituximab